2018
DOI: 10.12680/balneo.2018.222
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of disability after ischemic stroke depending on the circadian variation of stroke onset

Abstract: Introduction. The circadian variation of ischemic stroke onset is known, but its impact on recovery prognosis has been less studied. Materials and method. The study included 32 patients with ischemic stroke, admitted to Neurology Departments I and II of the Rehabilitation Hospital in Cluj-Napoca between 1 June 2008 and 31 December 2009 and followed up for 2 years, during 5 successive admissions. The diagnosis of ischemic stroke was defined according to updated World Health Organization criteria. The onset time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 10 publications
1
7
1
Order By: Relevance
“…However, the results are concordant, describing the best evolution of the functional score (mRS) from admission to discharge for patients with ischemic stroke onset in the 04.01-08.00 interval and the lowest score in the 20.01-24.00 interval, without statistically significant differences for NIHSS (8,11). The evolution of the mRS score is also consistent with the results of another study performed by us, in which the degree of disability was assessed based on ADL (activities of daily living) and IADL (instrumental activities of daily living) scores, with their least favorable evolution for ischemic stroke occurring in the nocturnal interval 00.01-06.00 and the greatest improvement for all time intervals during the first year after stroke (18).…”
Section: Discussionsupporting
confidence: 89%
“…However, the results are concordant, describing the best evolution of the functional score (mRS) from admission to discharge for patients with ischemic stroke onset in the 04.01-08.00 interval and the lowest score in the 20.01-24.00 interval, without statistically significant differences for NIHSS (8,11). The evolution of the mRS score is also consistent with the results of another study performed by us, in which the degree of disability was assessed based on ADL (activities of daily living) and IADL (instrumental activities of daily living) scores, with their least favorable evolution for ischemic stroke occurring in the nocturnal interval 00.01-06.00 and the greatest improvement for all time intervals during the first year after stroke (18).…”
Section: Discussionsupporting
confidence: 89%
“…In our study, we did not find significant predilection to age or sex in relation to time of stroke onset. Our finding was different from others who reported that onset during sleep was associated with younger age [7], and that males showed higher risk of large artery disease in the early morning [4]. Our stroke registry showed more frequent stroke onset in the first quarter of the day (morning), followed by the fourth quarter (night).…”
Section: Discussioncontrasting
confidence: 99%
“…Few studies found less incidence of stroke during sleeping hours but still higher in the morning than the afternoon [12,13]. In line with this it was reported that all subtypes of stroke showed predominant onset in the morning [14,15], while others showed two peaks one in the morning and another in the afternoon, with the least at night [7]. This circadian variation might be related to exogenous factors like sleep-awake cycles, physical activity, and up-right posture, and endogenous factors with their characteristic diurnal variation like blood pressure, autonomic system activity and hemostatic balance (with increased platelet agreeability, hypercoagulability and hypo-fibrinolysis in the morning [16][17][18].…”
Section: Discussionmentioning
confidence: 77%
“…Important improvements in the quality of life of cronic-ICH patients could be obtained by pursuing rehabilitation procedures in a balnear resort, at 6 month interval (21). However, other studies have demonstrated that between 1 and 2 years after stroke onset, disability (measured by modified Rankin score mRS, and activities of daily living ADL) did not improve after rehabilitation, and could even worsen in specific categories of patients (22,23).…”
Section: Discussionmentioning
confidence: 99%